U14 function in Saccharomyces cerevisiae can be provided by large deletion variants of yeast U14 and hybrid mouse-yeast U14 RNAs. - Li, D (1992)
The functional equivalency of yeast and mouse U14 RNAs was examined in Saccharomyces cerevisiae. The test RNAs included mouse U14 and several yeast-mouse bi- and tri-partite hybrid RNAs, all transcribed from yeast U14 gene signals. The ability of the heterologous RNAs to provide essential U14 function was assessed in a test strain containing a single glucose-repressible wild-type U14 gene. Mouse U14 was not functional in yeast. However, wild-type growth was supported by hybrid RNAs that included universal sequence elements from either source, two yeast-specific segments and a 5',3' terminal stem domain. The universal sequences include box C, box D and a sequence complementary to 18S rRNA, all shown previously to be required for function of yeast U14. Deletion and substitution mapping defined the yeast-specific elements and showed that a major portion of neighboring non-conserved RNA is dispensible. The results are discussed with a view to defining a minimal consensus U14 molecule.